2002
DOI: 10.1007/s005400200002
|View full text |Cite
|
Sign up to set email alerts
|

Onset of vecuronium-induced neuromuscular block after a long priming interval

Abstract: If the priming dose of vecuronium is given after a long priming interval (16 +/- 3 min), the time to onset of the neuromuscular block caused by the intubating dose of vecuronium is markedly shorter than when the conventional priming interval of 4 min is employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Vecuronium does not carry the risk of hyperkalemia but produces a longer duration of paralysis. 28 Before inducing muscle paralysis, the physician should be sure that the patient can be ventilated and intubated, particularly with a longer-acting agent, such as vecuronium. This might be difficult to ascertain because of the severe bronchospasm preventing ventilation by means of bag valve mask.…”
Section: Intubation Techniquementioning
confidence: 99%
“…Vecuronium does not carry the risk of hyperkalemia but produces a longer duration of paralysis. 28 Before inducing muscle paralysis, the physician should be sure that the patient can be ventilated and intubated, particularly with a longer-acting agent, such as vecuronium. This might be difficult to ascertain because of the severe bronchospasm preventing ventilation by means of bag valve mask.…”
Section: Intubation Techniquementioning
confidence: 99%
“…This finding was duplicated well with that reported by Toboada et al 3 and Huemer et al 35 who found that 4 min interval was optimal after different priming interval. On the contrary, Saitoh and his associates reported that 16 min interval was effective than 4 min vecuronium priming time to short the onset by 40 s. 30 Depression in swallowing reflex after atracurium and vecuronium priming was demonstrated in one study, but the corresponding T 1 % and TOF ratio were not measured. 28 Impairment of pulmonary function was demonstrated in other studies when using 20% of ED 95 vecuronium with reduction in forced expiratory volume in 1 s (FEV 1 ) and forced vital capacity.…”
Section: Discussionmentioning
confidence: 91%
“…Its early paresis will lead to increase in upper airway resistance, especially in supine position and breathing difficulty. 29,30 Voluntary hyperventilation and oxygen mask helped in allying any incidence of desaturation and sense of breathing difficulty. Moreover, it has been reported that unpleasant effects of priming dose were short-lasting and rather improved at the peak time of monitored effect of the priming dose at adductor pollicis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increase in potassium levels caused by succinylcholine might cause severe cardiac arrhythmias if the patient has hyperkalemia from respiratory acidosis. Vecuronium does not carry the risk of hyperkalemia but produces a longer duration of paralysis (28). Before inducing muscle paralysis, the physician should be sure that the patient can be ventilated and intubated, particularly with a longer-acting agent, such as vecuronium.…”
Section: Intubation Techniquementioning
confidence: 99%